PENERAPAN TEKNIK DISTRAKSI AUDIOVISUAL (FILM KARTUN ANIMASI) UNTUK MENURUNKAN KECEMASAN ANAK USIA PRA SEKOLAH SAAT PROSEDUR PEMBERIAN OBAT MELALUI INJEKSI - Sarini Sarini; Desty Lismayanti; Yanti Rosmiyanti; Sumitro Sumitro; Okti Rahayu Asih; Difa Nur Fadillah (Bajang Institute, 2025)
Hospitalization is a crisis situation for children, when they are sick and must receive care in the hospital; the child tries to adapt to a new environment, unfamiliar people, and separation (Handayani & Daulima, 2020). Being separated from parents often triggers emotional responses in the form of anxiety, which can cause trauma during treatment, both in the long term and in the short term (Padila et al, 2020). When children face too much stress during hospitalization, this can worsen their development. The aim of this study is to determine the effect of audiovisual distraction techniques on the anxiety level of preschool children before and after the drug administration procedure by injection. Thus, this is a non-pharmacological intervention that can reduce anxiety and divert attention by carrying out distraction techniques. Data collection was carried out using a descriptive design method with a case study approach on two respondents. Data were collected through interviews, observation, and physical examination.This study’s results indicate an effect on reducing anxiety in preschool-aged children during the procedure of administering medication via injection using an audiovisual distraction technique (animated card film) (Novitasari,et al, 2021).